2012
DOI: 10.1016/j.jcmg.2011.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Late Gadolinium Enhancement in Clinical Outcomes for Hypertrophic Cardiomyopathy

Abstract: Late gadolinium enhancement by CMR has prognostic value in predicting adverse cardiovascular events among HCM patients. There are significant relationships between LGE and cardiovascular mortality, heart failure death, and all-cause mortality in HCM. Additionally, LGE and SCD/aborted SCD displayed a trend toward significance. The assessment of LGE by CMR has the potential to provide important information to improve risk stratification in HCM in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
202
1
13

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(230 citation statements)
references
References 29 publications
9
202
1
13
Order By: Relevance
“…The mean age of our population (56.4±17.0 years) was older than in most studies in the literature 5,11,12 and included few patients in the age-group most associated with sudden death (<35 years). Most were asymptomatic or mildly symptomatic, as in other published series.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The mean age of our population (56.4±17.0 years) was older than in most studies in the literature 5,11,12 and included few patients in the age-group most associated with sudden death (<35 years). Most were asymptomatic or mildly symptomatic, as in other published series.…”
Section: Discussionmentioning
confidence: 80%
“…In a recent meta-analysis of four studies with a total of 1063 HCM patients, Green et al 5 confirmed the high prevalence of LGE (60%) and its correlation with adverse cardiovascular events (cardiac death, heart failure death, and all-cause mortality), although it was not associated with sudden death or aborted sudden death and did not add value to traditional clinical risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, attention has focused on contrast-enhanced CMR with LGE to non-invasively identify myocardial fibrosis, the potential arrhythmogenic substrate in HCM. [14][15][16][17][18] Early studies demonstrated that patients with HCM and evidence of LGE on CMR have increased rates of non-sustained ventricular tachycardia on ambulatory Holter monitoring compared with patients without LGE, raising the concept that LGE represents a substrate for generation of malignant ventricular arrhythmias. 14 This notion led to several outcome studies, each with relatively small patient cohorts, evaluating the presence of LGE on CMR and demonstrating that patients with HCM with LGE were at increased risk of cardiovascular mortality.…”
Section: Sudden Deathmentioning
confidence: 99%
“…Contrast-enhanced CMR has emerged as an excellent tool for improving risk stratification of HCM patients. Although the data are still limited in this regard, there are several studies which have highlighted that the presence and extent of LGE can improve risk stratification of HCM patients [14,[18][19][20]. The relevant studies are summarized in Tables 1-4.…”
Section: Late Gadolinium Enhancement and Scdmentioning
confidence: 99%